Optimization of Process Variables for the Production of Virgin Coconut Oil from Selected Cocos Nucifera Varieties under Fresh-Dry Method - N., Muthukkannan; T., Balasaravanan (International Journal of Scientific Research in Biological Sciences, 2019)
Virgin Coconut Oil (VCO) was prepared from four coconut varieties viz., West Coast Tall, Arasampatti Tall, Deejay and Tiptur Tall. The Fresh-Dry methodology was optimized by three common variable parameters like temperature viz., 30±1ºC, 35±1ºC, 40±1º C, 45±1ºC, Drying intervals viz., 24hrs, 36hrs, 48 hrs, 60hrs and fruit maturity like 10, 11, 12 and 13 month old coconuts was taken to estimate the yielding efficiency of VCO .The yielding efficiencies are calculated from the four Coconut varieties by comparing the total percentage of Oil extracted from Soxhlet method. Among the four, the maximum yielding efficiency 95.33% was obtained in WCT Coconuts drying with 45º C. In the second process variable, where the maximum yield efficiency was showed that is 93.06% with 48 hrs drying. The third process variable showed the same maximum value of 93.06% as in second process variable by employing 12 month old coconuts The coconut varieties are taken in this research study, showed different yield composition of fatty acid profile especially the lauric acid percentage, which was registered maximum that is 51.20% at “WCT Coconuts” and in other coconut varieties such as AT, DJ and TT Coconuts were noted as 50.10%, 49.23% and 48.55% respectively.